Analisis Pengaruh Kepuasan Kerja, Budaya Organisasi dan Kompetensi terhadap Organizational Citizenship Behavior pada PT. Mubarak Ainama Kunt Surabaya - Khoirul Mahmudi; Jun Surjanti (Jurnal Ilmu Manajemen, 2020)
This study aims to examine and analyze the influence of job satisfaction, organizational culture, dan competence on Organizational Citizenship Behavior in PT. Mubarak Ainama Kunt Surabaya. This research is quantitative. The data that will be used in this study is systematic data (numbers) which will produce conclusions that can be generalized. The data in this study use primary and secondary data. Primary data in the form of data obtained through questionnaires to 42 respondents as research samples and secondary data in the form of data company profile company. The statistical analysis used in this study is multiple linear regression. The measurement scale of this study uses a Likert scale The results of this study are job satisfaction has a significant positive effect on Organizational Citizenship Behavior. This shows that better job satisfaction in the company, the higher the Organizational Citizenship Behavior felt by employees. Organizational culture has a significant positive effect on Organizational Citizenship Behavior. This shows that the better the organizational culture in the company, the higher the Organizational Citizenship Behavior felt by employees. Competence has no significant effect on Organizational Citizenship Behavior. Implementation of competencies is carried out conditionally according to the needs of the company not bound by a certain period. This shows that the good or bad implementation of competencies in the company will not affect the increase or decrease in Organizational Citizenship Behavior employees at PT. Mubarak Ainama Kunt Surabaya.